Thermogenic adipocytes promote HDL turnover and reverse cholesterol transport - Alexander Bartelt (Nature Portfolio, 2017)
Activation of brown adipose tissue (BAT) reduces the development of atherosclerosis in animal models. Here the authors show that BAT activation also increases reverse cholesterol transport and turnover of high-density lipoprotein, which likely contributes to the anti-atherosclerotic effect of BAT activation.